Determination of child guardianship as a requirement for taking guarantee of property rights certificates - Ananda Farhan Nizzar; Siti Malikhatun Badriyah (Universitas Wiralodra, 2023)
The purpose of this study is to identify, describe, and analyze the reasons why banks require the establishment of child guardianship as a requirement for taking ownership certificates. In addition, this study also aims to identify the factors and legal consequences of the guardianship arrangement, as well as how the trusteeship process ends. The research method used is a normative legal approach with a juridical-philosophical approach. The data used in this study were obtained from primary and secondary legal materials through library research. The data analysis technique used is descriptive analysis technique. The results of this study reveal that banks require the establishment of guardianship as a requirement because it is used as authentic evidence of the existence of legal guardianship by the authorities. Notary can act as a representative for minors who are represented by parents who are still alive. This applies especially when the parent who took the loan from the bank has passed away, but it is necessary to have a guardian to take the collateral for the certificate of ownership whose installments have been paid to the bank. This step is also necessary for future destinations on a certain date as well as related parties involved in it. The importance of the guardianship deed through a notary in the family is the basis for consideration, considering that the bank cannot provide collateral if the conditions included in taking the guarantee are not fulfilled. This includes cases where deceased creditors still have minor children. Although the law states that biological parents who are still alive have the authority to arrange the deed of sale and purchase of land rights for children who have lost one of their parents, in the context of banking, the existence of a trusteeship is recognized as an important step in ensuring the completeness of the collateral collection documents.